1990
DOI: 10.1002/cjce.5450680210
|View full text |Cite
|
Sign up to set email alerts
|

Continuous crystallization of potash alum: MSMPR kinetics

Abstract: The crystallization kinetics of potash alum (aluminium potassium sulphate) from aqueous and aqueous acetone solutions respectively in a continuous mixed‐suspension, mixed‐product‐removal (MSMPR) crystallizer (capacity 4 L) are reported. Growth and nucleation rates are determined by direct model estimation via the population balance analysis of crystal size distribution measured using laser light scattering and sieve analysis. The overall growth rate during drowning‐out precipitation strongly decreases with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The crystallization kinetics of potash alum from aqueous solutions in a continuous MSMPR crystallizer were recently reported by JONES and MYDLARZ (1990). Figure 5 shows a curved log-cumulative number distribution typical of those obtained in the case of drowning-out precipitation of potash alum with diluted acetone.…”
Section: Potash Alum Datamentioning
confidence: 88%
“…The crystallization kinetics of potash alum from aqueous solutions in a continuous MSMPR crystallizer were recently reported by JONES and MYDLARZ (1990). Figure 5 shows a curved log-cumulative number distribution typical of those obtained in the case of drowning-out precipitation of potash alum with diluted acetone.…”
Section: Potash Alum Datamentioning
confidence: 88%
“…mixedproduct-removal draft-tube crystallizer reported recently (Jones and Mydlarz, 1990) indicated that zero-size nucleation rates for cooling crystallization and drowning-out precipitation, however, are approximately the same in both modes of creating supersaturation, indicating that secondary nucleation predominates. mixedproduct-removal draft-tube crystallizer reported recently (Jones and Mydlarz, 1990) indicated that zero-size nucleation rates for cooling crystallization and drowning-out precipitation, however, are approximately the same in both modes of creating supersaturation, indicating that secondary nucleation predominates.…”
Section: Effect Of Precipitant Dilutionmentioning
confidence: 95%
“…
Crystal slurries produced both by cooling and by precipitation with acetone from aqueous solution in a continuous MSMPR crystallizer reported earlier (Jones and Mydlarz, 1990) are analysed in terms of the effect of their crystal size distribution and shape on filtrability characteristics.Crystals produced by precipitation are much smaller but more highly agglomerated than those from cooling crystallization and give rise to lower filter bed permeabilities, a performance which is slightly improved by precipitant dilution. The overall particle size is, however, similar in both modes and is relatively insensitive to crystallizer operating conditions.
…”
mentioning
confidence: 99%
See 2 more Smart Citations